2009
DOI: 10.2527/jas.2008-1220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone-releasing hormone treatment on milk production and plasma hormones and metabolites in lactating Japanese Black cows under negative energy balance1

Abstract: The current study was performed to clarify the effects of GHRH treatment on milk production and plasma hormones and metabolites in lactating Japanese Black cows (a beef breed) under negative energy balance (EB). Ten multiparous lactating beef cows were offered a normal-energy diet daily (110% of ME requirements for maintenance and lactation) until 5 d in milk (DIM) to standardize the cows before dietary treatment. From 6 DIM to the final days (63 DIM) of the experiment, the cows were allotted to experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…In addition, we also observed that NEB raised the plasma concentrations of BHBA, NEFA, TG and UN, while it lowered those of GLU and TC. Consistent with the findings of a previous experimentally induced NEB study, these results likewise indicated the occurrence of NEB in the present study, more concurrence between this investigation and previous studies also being the latter’s confirmation of the relationship between energy metabolites and follicular development ( 12 , 17 , 24 , 29 ). Higher plasma BHBA and NEFA concentrations and lower GLU concentrations were not conducive to ovulation in dairy cows ( 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we also observed that NEB raised the plasma concentrations of BHBA, NEFA, TG and UN, while it lowered those of GLU and TC. Consistent with the findings of a previous experimentally induced NEB study, these results likewise indicated the occurrence of NEB in the present study, more concurrence between this investigation and previous studies also being the latter’s confirmation of the relationship between energy metabolites and follicular development ( 12 , 17 , 24 , 29 ). Higher plasma BHBA and NEFA concentrations and lower GLU concentrations were not conducive to ovulation in dairy cows ( 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…The mean plasma urea concentration of whole trial (mg/ dl) was significantly (P<0.05) higher in T2 (26.59), but there was no difference between control (24.90) and T1 (25.37) (Table 4). However, it lies within the normal range in all the experimental groups as reported earlier (Dhali et al 2005;Shingu et al 2009). Contrary to our findings, Kumar and Das (2006) reported that supplementation of 100 ppm and 200 ppm niacin had no significant effect on serum urea-N in male buffalo calves.…”
Section: Plasma Ureasupporting
confidence: 85%
“…On the other occasion, GHRH treatment might induce insulin resistance in lactating Japanese Black cows (Shingu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%